2022
DOI: 10.1093/ofid/ofac492.1595
|View full text |Cite
|
Sign up to set email alerts
|

1970. SARS-CoV-2 T-cell specific responses in allogeneic hematopoietic stem cell transplant recipients after second and third dose of BNT162b2 mRNA vaccine

Abstract: Background Cell-mediated immunity (CMI) after anti-Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV)-2 vaccines has been poorly explored in recipients of allogeneic hematopoietic stem-cell transplantation (HSCT), especially with regard to the 3rd dose (booster). Aim of the study was to assess the specific T-cell responses before and after the 3rd dose of BNT162b2 mRNA vaccine in a cohort of allogeneic HSCT recipients, and compare it with healthy donors (HD). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Six studies evaluated the cellular immune response to a third vaccine dose, focusing on interferon-gamma (IFNγ) production by CD4+ and CD8+ T-lymphocytes. Additional assessments included IL-2 release, CD154 upregulation, and tumor necrosis factor alpha (TNF-α) production [29,[33][34][35][36][37]. Albiol et al 's study [33] found that 76.6% of patients vaccinated within three to 24 months (G1) and 94.4% vaccinated after 24 months (G2) from HSCT had a positive response, with no significant statistical difference.…”
Section: Cellular Response After Third Dosementioning
confidence: 99%
See 1 more Smart Citation
“…Six studies evaluated the cellular immune response to a third vaccine dose, focusing on interferon-gamma (IFNγ) production by CD4+ and CD8+ T-lymphocytes. Additional assessments included IL-2 release, CD154 upregulation, and tumor necrosis factor alpha (TNF-α) production [29,[33][34][35][36][37]. Albiol et al 's study [33] found that 76.6% of patients vaccinated within three to 24 months (G1) and 94.4% vaccinated after 24 months (G2) from HSCT had a positive response, with no significant statistical difference.…”
Section: Cellular Response After Third Dosementioning
confidence: 99%
“…Another study by Ram et al [29] reported that 83% of CAR-T patients (5/6) and 100% of allo-HSCT patients (10/10) showed a positive cellular response post-third-dose injection. Furthermore, Marco et al [36] demonstrated a significant augmentation in the SARS-CoV-2 S specific T-cell responses among HSCT recipients after third dose by performing a before-after analysis.…”
Section: Cellular Response After Third Dosementioning
confidence: 99%